USE OF RHETORICAL INTERROGATIVES IN ADVERTISING LANGUAGE - Yusupova Kamola (Scholar Express Journal, 2023)
This article analyzes that when expressing imperative content through rhetorical interrogative constructions, although the meaning of motivation and coercion is strict, the expression is soft, expressiveness leads in the semantic structure of rhetorical interrogative sentences, and therefore, they are an extremely necessary element of the advertising text
Keywords: advertising text; imperative content; rhetorical interrogative sentences